Gender and Muslim constructions of exegetical authority : a rereading of the classical genre of Qur'ān commentary - Geissinger, Aisha. (Islamic History and Civilization, 2015)
A number of classical Sunnī Quran commentaries quote several different types of exegetical materials attributed to a few female figures from the first century A.H/seventh century C.E.-āthār, ḥadīths, legal opinions and variant readings, as well as lines of poetry. In Gender and Muslim Constructions of Exegetical Authority , Aisha Geissinger provides a comprehensive introduction to such quotations, and offers an analysis of their place and significance within the pre-modern genre of Quran commentary, demonstrating that key hermeneutical concepts in classical quranic exegesis ( tafsīr ) are gendered. Bringing together materials which have not previously been examined in detail and utilising gender as a lens through which to study them, this work provides a new approach to the study of pre-modern tafsīr .